2012
DOI: 10.5897/ajb11.3289
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity analysis and subspecies classification of Thailand rice landraces using DNA markers

Abstract: Genetic diversity among 126 rice accessions, including 110 Thai landraces and 16 varieties used as subspecies reference, were evaluated by three types of DNA markers, InDel (Insertion/Deletion), intersimple sequence repeat (ISSR) and simple sequence repeat (SSR) markers. Twelve InDel primer pairs, based on DNA sequence polymorphism between '93-11' (indica) and 'Nipponbare' (japonica), were used to identify subspecies of landraces. Most of the local rice samples had either '93-11' alleles or 'Nipponbare' allele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 19 publications
1
4
0
Order By: Relevance
“…The results showed a good consistency between STRUCTURE and DAPC. The population structure analysis using these approaches suggested that the Thai rice landraces could be divided into two main subpopulations, corresponding to indica and japonica groups, similar to the previous reports [21,23,24]. However, the majority of accessions present in our panel were indica rice.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The results showed a good consistency between STRUCTURE and DAPC. The population structure analysis using these approaches suggested that the Thai rice landraces could be divided into two main subpopulations, corresponding to indica and japonica groups, similar to the previous reports [21,23,24]. However, the majority of accessions present in our panel were indica rice.…”
Section: Discussionsupporting
confidence: 86%
“…To effectively utilize this germplasm, an assessment and classification of the diversity is necessary. While studies on genetic diversity are available for many rice collections around the world [19,20], those for Thai rice germplasm have been conducted on limited sets of accessions [21][22][23][24][25]. According to the previous studies on the genetic structure of Thai rice evaluated using indel and simple sequence repeat (SSR) markers, two distinct groups of rice accessions have been revealed to correspond to indica and japonica groups [23,24].…”
Section: Introductionmentioning
confidence: 99%
“…Molecular markers are able to reveal variation present between them at DNA level (Ni et al 2002, Chakravarthi andNaravaneni, 2006). These DNA-based markers are highly precise, dependable and not prone to environmental conditions and fluctuations [9][10][11][12][13].…”
Section: Inroductionmentioning
confidence: 99%
“…Moreover, there is a higher level of diversity in Thai rice accessions compared to selected rice accessions obtained from International Rice Research Institute (IRRI) germplasm based on InDel markers (Chakhonkaen et al 2012). Limited data shows that Upland Thai rice forms a cluster of tropical japonica (Pathaichindachote et al 2019;Chakhonkaen et al 2012;Kladmook et al 2012), while lowland rice forms indica clusters.…”
Section: Introductionmentioning
confidence: 99%